2023
DOI: 10.1098/rstb.2022.0009
|View full text |Cite
|
Sign up to set email alerts
|

Temperature modifies trait-mediated infection outcomes in aDaphnia–fungal parasite system

Abstract: One major concern related to climate change is that elevated temperatures will drive increases in parasite outbreaks. Increasing temperature is known to alter host traits and host–parasite interactions, but we know relatively little about how these are connected mechanistically—that is, about how warmer temperatures impact the relationship between epidemiologically relevant host traits and infection outcomes. Here, we used a zooplankton–fungus ( Daphnia dentifera–Metschnikowia bicuspidata … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…We scanned the anterior and posterior of the gut, where spores are most likely found penetrating into the host's body cavity (Stewart Merrill et al, 2019). We counted the number of spores, split into two categories (sensu Stewart Merrill et al, 2019): embedded spores (i.e., partially embedded in the gut epithelium; Figure 1b) and hemocoel spores (i.e., penetrated into the body cavity; Figure 1b); this allows us to quantify gut resistance (i.e., the extent to which the gut epithelium acts as a barrier to infecting spores) as the number of embedded spores divided by the total number of attacking spores (embedded spores + hemocoel spores), as done in earlier studies (Stewart Merrill et al, 2019; Sun, Dziuba, Jaye, et al, 2022). Meanwhile, we determined gut epithelium thickness by averaging the height of three haphazardly selected epithelium cells at the anterior end of the gut (Sun, Dziuba, Jaye, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We scanned the anterior and posterior of the gut, where spores are most likely found penetrating into the host's body cavity (Stewart Merrill et al, 2019). We counted the number of spores, split into two categories (sensu Stewart Merrill et al, 2019): embedded spores (i.e., partially embedded in the gut epithelium; Figure 1b) and hemocoel spores (i.e., penetrated into the body cavity; Figure 1b); this allows us to quantify gut resistance (i.e., the extent to which the gut epithelium acts as a barrier to infecting spores) as the number of embedded spores divided by the total number of attacking spores (embedded spores + hemocoel spores), as done in earlier studies (Stewart Merrill et al, 2019; Sun, Dziuba, Jaye, et al, 2022). Meanwhile, we determined gut epithelium thickness by averaging the height of three haphazardly selected epithelium cells at the anterior end of the gut (Sun, Dziuba, Jaye, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This experiment used the “Standard” lab lines of D. dentifera and M. bicuspidata originally isolated from a lake in Barry County, Michigan. We describe the maintenance of the D. dentifera and M. bicuspidata used in this study in more detail elsewhere (Sun, Dziuba, Jaye, et al, 2022). Immediately prior to this experiment, D. dentifera were maintained in standardized conditions (a 16:8 photoperiod at 22°C) for three generations and fed three times a week with a phytoplankton food ( Ankistrodesmus falcatus , 20,000 cells/ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the impact of environmental temperatures on disease outbreaks, two papers focus on changes in mechanisms underpinning the ability of parasites to infect [ 18 ] and of hosts to resist [ 19 ]. In effect, these papers take care to start from the beginning, where the host and parasite first meet, using the planktonic crustacean Daphnia and its bacterial parasites.…”
Section: Theme 1: Climate Change and Infection Outcomesmentioning
confidence: 99%
“…Like most hosts, waterfleas have physical barriers to infection and also have cellular immune responses. In detailed experiments, Sun et al [19] found that warming affected these defence traits differently, with consequences for infection outcomes. Disease spread can also depend on how temperature interacts with traits in host communities [20,21].…”
Section: Introductionmentioning
confidence: 99%